Genetic association of NOS1 exon18, NOS1 exon29, ABCB1 1236C/T, and ABCB1 3435C/T polymorphisms with the risk of Parkinson's disease: A meta-analysis. Issue 40 (October 2016) - Huang, Hongbin; Peng, Cong; Liu, Yong; Liu, Xu; Chen, Qicong; Huang, Zunnan
Abstract: Background: Parkinson's disease (PD) is the second most frequent neurodegenerative disorder. Previous publications have investigated the association of NOS1 and ABCB1 polymorphisms with PD risk. However, those studies have provided some contradictory results. Methods: Literature searches were performed using PubMed, Embase, PDgene, China National Knowledge Infrastructure database, and Google Scholar. Odds ratios (ORs) with 95% confidence intervals (CIs) were applied to evaluate the strength of association. Results: The analysis results indicated that NOS1 exon18 polymorphism was associated with developing PD in 4 genetic models (allelic: OR = 1.25, 95%CI 1.09–1.44, P = 0.001; homozygous: OR = 1.79, 95%CI 1.32–2.45, P < 0.001; recessive: OR = 1.70, 95%CI 1.26–2.28, P < 0.001; dominant: OR = 1.22, 95%CI 1.02–1.46, P = 0.03), whereas exon29 polymorphism was not correlated to PD susceptibility. In addition, ABCB1 1236C/T polymorphism was related to PD in the recessive (OR = 0.80, 95%CI 0.66–0.97, P = 0.025) and overdominant (OR = 1.21, 95%CI 1.03–1.43, P = 0.02) models, which might indicate the opposite effects of 2 minor variants of this locus on Parkinson's disease. However, this associated result was not robust enough to withstand statistically significant correction. On the other hand, no association was found between ABCB1 3435C/T polymorphism and the predisposition to PD in 5 genetic models, and such an absence of relationship was further confirmed by subgroup analysis in Caucasians and Asians. Whether the polymorphisms of these 4 loci were linked to PD or not, our study provided some interesting findings that differ from the previous results with regard to their genetic susceptibility. Conclusion: The NOS1 exon18 and ABCB1 1236C/T variants might play a role in the risk of Parkinson's disease, whereas NOS1 exon29 and ABCB1 3435C/T polymorphisms might not contribute to PD susceptibility.